(3HOGFY GdRghQ aj hbGFY GdOghQ (B( (3bWYI ef JGQjN eUQ (B)s - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO Ydjge YQV Je jeVhG Hge Edi GdOaJQ OGQ ajNQL ef GSeg HGdGbQGM Yf Pdc ajbY dge cdaI GdbGVi s
(3BNQgG (B:s
(3aeUdGg eOI WhjdI aTcGgeG ef YfO GdOaJQ OGQ aGQSd NdageG adeG MVQ s
(3Je JhKjbI ef NdGd eNWhWGJ CNQi cGedI ddcJGHs
(3hgh eWHhYs
(3hgPg GdbWYI JJMOK Yf aJQI GdSdWGf GdZhQi hSdje NGfs
(3hgj JhGab eG ai WHYI HhdGb ef U (B123 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B236s
Keywords: (3eJaQbGJs